Tracing Chinese international students’ psychological and academic adjustments in uncertain times: An exploratory case study in the United Kingdom - Liu, Guangxiang; Li, Wentao; Zhang, Yueshan (Frontiers in Psychology, 2022)
The worldwide spread of COVID-19 has exerted tremendous influences on the well-being of international students and the sustainable development of higher education. The current study adopts an eight-month exploratory case study to trace eight Chinese international students’ psychological and academic adjustments in the UK amid the COVID-19 pandemic. Emerging from the qualitative data constitutive of semi-structured interviews, self-reflection writings, memoing, together with stimulated-recall interviews, findings have demonstrated the three main types of obstruction for such students’ adjustments in the foreign land including COVID-specific challenges (i.e., the threat of infect, reduced access to university facilities and resources); COVID-enhanced challenges (i.e., anxiety exacerbated by parents and social media use, anti-Asian racism and hate incidents); and language barriers and cultural differences as long-standing issues. Students’ previous lockdown experience, individual resilience, development of monocultural friendship patterns, and institutional provision and support are all factors that have contributed to their ability to overcome or at least mitigate the psychological and academic difficulties. The study offers insight into the impacts of COVID-19 on international students, providing implications that could contribute to the sustainable adjustments of international students in times of disruptive events and inform future responses to global health crises from individual and higher education perspectives.